Distribution Characteristics and Formula Revision of Lightning Current Amplitude and Cumulative Probability in Zhejiang Province - Xia, Li; Nannan, Song; Yanfeng, Fan; Yinping, Liu; Qing, Liu; Xiaolin, Guan; Pei, Miao (Frontiers in Environmental Science, 2022)
The cumulative probability distribution of lightning current amplitude can reflect the lightning activity and is important for the lightning protection engineering technology. Based on the lightning location data from 2009 to 2019, the distribution characteristics of lightning current amplitude and cumulative probability are studied. The results show that a total of 8 634 858 lightning flashes occur in Zhejiang for 11 years. And the negative flashes are much higher than the positive ones, accounting for 87.44%. The percentage of lightning current amplitude between 2-100 kA is 94.3%. The average amplitude of positive flashes is significantly higher than that of negative flashes. For the current amplitude of positive flashes, peak occurs in March, and gradually decreases with the increase of the month, lowest in December. But the monthly distribution of negative flashes is relatively concentrated, mainly from February to October. When the lightning current amplitude is higher than 25.5 kA, the cumulative probability of positive flashes is significantly higher than that of negative flashes, and vice versa. The cumulative probability distribution of negative flashes is closer to that of total flashes, and is significantly different from that of positive flashes. In order to get a more suitable cumulative probability formula of lightning current amplitude and corresponding parameters in Zhejiang, the Levenberg-Marquardt method is used. By fitting the measured data with the formulas recommended by Institute of Electrical and Electronics Engineers (IEEE) and Electric Power Industry Standard of China (Code for Design of Overvoltage Protection and Insulation Coordination for AC Electrical Installations GB/T 50064-2014) respectively, the correlation coefficients of different polarities are obtained. Through comparison, it is found that the formula recommended by IEEE can more objectively reflect the probability distribution characteristics in Zhejiang, and the accuracy of the derived formula is verified by using the lightning current data in 2020. It shows that the curve based on the measured values is consistent with that fitted by IEEE formula, but quite different from that fitted by GB/T 50064-2014 formula.